Probing the origin and stability of bivalency in copper based porous coordination network and its application for H2S gas capture - Nishesh Kumar Gupta; Eun Ji Kim; Jiyeol Bae; Kwang Soo Kim (Scientific Reports, 2022)
Abstract A bivalent Cu(I,II) metal–organic framework (MOF) based on the 4,4′,4″-s-Triazine-2,4,6-triyl-tribenzoate linker was synthesized via a solvothermal method. The MOF possessed 43.8% of the Cu sites as Cu+ with a surface area of 1257 m2 g−1. The detailed spectroscopic analysis confirmed dimethylformamide (DMF) solvent as the reductant responsible for Cu+ sites in the synthesized MOF. The Cu+ sites were easily accessible and prone to oxidation in hot water or acidic gas environment. The MOF showed water-induced structural change, which could be partially recovered after soaking in DMF solvent. The synthesized MOF showed a high hydrogen sulfide (H2S) uptake capacity of 4.3 mmol g–1 at 298 K and an extremely low H2S pressure of 0.0005 bar. The adsorption capacity was the highest among Cu-based MOFs with PCN-6-M being regenerable, which made it useful for deep desulfurization applications. The adsorbed H2S was mineralized to sulfide, sulfur, and sulfates, mediated by the Cu+/Cu2+ redox cycle in the presence of adsorbed water and molecular oxygen. Thus, the study confirmed that DMF as a reductant is responsible for the origin of bivalency in PCN-6-M and possibly in other Cu-based MOFs reported in the literature. Also, the developed MOF could be a potential candidate for flue gas desulfurization and gas purification applications.